Hydrogeochemical Characterization, and Suitability Assessment of Drinking Groundwater: Application of Geostatistical Approach and Geographic Information System - Ghani, Junaid; Ullah, Zahid; Nawab, Javed; Iqbal, Javed; Waqas, Muhammad; Ali, Asmat; Almutairi, Mikhlid H.; Peluso, Ilaria; Mohamed, Hanan R. H.; Shah, Muddaser (Frontiers in Environmental Science, 2022)
Arsenic (As) contamination in drinking groundwater sources is a common environmental problem in Pakistan. Therefore, we collected a total of (n=81) drinking groundwater samples from various groundwater sources, from two districts’ namely Ghotki (n=44) and Nawab Shah (n=37) of Sindh, Province, Pakistan. The current research was aimed to investigate the hydrogeochemistry of groundwater with elevated arsenic (As), its effect on the health of local population living in the study area, potential sources of groundwater variables and suitability of gorundwater for ingestion motive. The results showed that groundwater samples variables of both districts had moderate to high concentration levels. The cations concentrations were observed in decreasing order of Na+ > Ca+ > Mg+ > K+, for both districts, while anions abundance was HCO3− > Cl− > SO42− > F− > NO3− in the Ghotki, and HCO3− > SO42− > Cl− > NO3− > F− in the Nawab Shah, respectively. Arsenic (As) had low to high concentration levels in both districts, observed with average values of 10.1 μg/L and 21.0 μg /L in the Ghotki and Nawab Shah, respectively. The water type was mixed CaMgCl type in both districts, while the groundwater sources were saturated for CO3 minerals indicated by the saturation indices results. Principal component analysis showed the geogenic source of ion exchange, dissolution of minerals, weathering of host rocks and anthropogenic input of industrial activities, agricultural practices and domestic waste for groundwater contamination. The water quality index (WQI) exhibit that majority of groundwater samples (73.6% of Ghotki), and (65.7% of Nawab Shah) were suitable for drinking. The non-carcinogenic risk (HQ) values of As were (>1) in groundwater samples of the Ghotki and Nawab Shah, while high mean HQ value (8.78 × 100) was recorded for children in Nawab Shah. The carcinogenic risk (CR) values of As were significantly higher than the maximum threshold CR value (1 × 10-4). This study emphasized that monitoring strategies are substantially needed to mitigate the As contamination in order to reduce the potential health risk.